Implementation of Learning Theory in the Curriculum of MTs Fatahillah: An Analysis of Teaching Strategies Based on Cognitivism and Constructivism - Erihadiana, Mohamad; Algifari, Muhaemin; Fahri, Muhammad Raja Iqbal (CV. Rayyan Dwi Bharata, 2025)
The understanding and application of cognitive and constructivist theories in teaching at MTs Fatahillah demonstrate variations in implementation effectiveness. Cognitivism, which emphasizes mental processes and information processing, is applied through visual aids and analytical exercises, such as concept maps in Fikih subjects. This helps students understand the material deeply and think critically. Meanwhile, constructivism emphasizes active experiences and interaction in the learning process, such as group projects to study moral values. Although this approach has a positive impact on students' intellectual and social skills development, its implementation faces challenges, such as limited time and resources and students' readiness. The implementation of the 2013 Curriculum at MTs Fatahillah, which is based on religious values and character development, provides a foundation for integrating these two theories despite limitations. Support from the school is needed to optimize teacher training and improve facilities to support active learning. Thus, despite the obstacles, the adaptation of cognitivism and constructivism can enhance student engagement and provide meaningful learning experiences, in line with holistic educational goals.